2011
DOI: 10.1177/0165025411406860
|View full text |Cite
|
Sign up to set email alerts
|

The confluence of adverse early experience and puberty on the cortisol awakening response

Abstract: Associations between early deprivation/neglect in the form of institutional care with the cortisol awakening response (CAR) were examined as a function of pubertal status among 12- and 13-year-old post-institutionalized youth. CARs indexed hypothalamic-pituitary-adrenocortical reactivity. Post-institutionalized youth were compared to youth adopted internationally from foster care (adoption control) and to nonadopted youth reared in families comparable in parental education and income to the adoptive families. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 42 publications
12
85
0
Order By: Relevance
“…30 However, as the majority of our participants had not entered puberty at the time of the study, we could not investigate whether neural markers of ELS are reversed after pubertal transitions as evidenced for hypothalamic-pituitary-adrenal axis reactivity in previous research. 54 A number of caveats should be considered with respect to the present data. First, research with children with ELS is complicated by incomplete biographical records from the children's life before placement, previous environmental conditions, and their unknown genetic makeup.…”
Section: Figure 2 Functional Connectivity Results (Psychophysiologicamentioning
confidence: 83%
“…30 However, as the majority of our participants had not entered puberty at the time of the study, we could not investigate whether neural markers of ELS are reversed after pubertal transitions as evidenced for hypothalamic-pituitary-adrenal axis reactivity in previous research. 54 A number of caveats should be considered with respect to the present data. First, research with children with ELS is complicated by incomplete biographical records from the children's life before placement, previous environmental conditions, and their unknown genetic makeup.…”
Section: Figure 2 Functional Connectivity Results (Psychophysiologicamentioning
confidence: 83%
“…Both abnormally high and low cortisol levels, reflecting aberrant HPA function, have been linked with early life stressors including severe childhood abuse, and post-institutionalisation (Doom et al 2013;Quevedo et al 2012), with recent evidence of heightened cortisol levels in adult schizophrenia participants with a history of childhood trauma (Braehler et al 2005). In accordance with the diathesis stress model, evidence also suggests there may be an ability in healthy individuals to 'bounce back' from childhood trauma, confirmed by an attenuated Dexamethasone/CRH response in individuals exposed to early trauma (Klaassens 2010).…”
Section: Neurobiology Of Stressmentioning
confidence: 99%
“…B3PH2) than in adult females. An earlier study also showed a higher level of cortisol secretion in the CAR of healthy girls at the mid-late Tanner pubertal stages than those at the pre-early Tanner pubertal stages [32] . Based on the results of present and previous studies, progression of puberty in girls does not seem to be associated with the magnitude and pattern of cortisol rises from waking until 30 min post-waking; rather, it is associated with an increase in the levels of cortisol secretion in the CAR.…”
Section: Discussionmentioning
confidence: 80%